Bedside hyperspectral imaging indicates a microcirculatory sepsis pattern: an observational study - Dietrich, Maximilian; Marx, Sebastian; Forst, Maik von der; Bruckner, Thomas; Schmitt, Felix; Fiedler-Kalenka, Mascha; Nickel, Felix; Studier-Fischer, Alexander; Müller, Beat P.; Hackert, Thilo; Brenner, Thorsten; Weigand, Markus A.; et al. (Microvascular research, 2021)
Introduction - Microcirculatory alterations are key mechanisms in sepsis pathophysiology leading to tissue hypoxia, edema formation, and organ dysfunction. Hyperspectral imaging (HSI) is an emerging imaging technology that uses tissue-light interactions to evaluate biochemical tissue characteristics including tissue oxygenation, hemoglobin content and water content. Currently, clinical data for HSI technologies in critical ill patients are still limited. - Methods and analysis - TIVITA® Tissue System was used to measure Tissue oxygenation (StO2), Tissue Hemoglobin Index (THI), Near Infrared Perfusion Index (NPI) and Tissue Water Index (TWI) in 25 healthy volunteers and 25 septic patients. HSI measurement sites were the palm, the fingertip, and a suprapatellar knee area. Septic patients were evaluated on admission to the ICU (E), 6 h afterwards (E+6) and three times a day (t3-t9) within a total observation period of 72 h. Primary outcome was the correlation of HSI results with daily SOFA-scores. - Results - Serial HSI at the three measurement sites in healthy volunteers showed a low mean variance expressing high retest reliability. HSI at E demonstrated significantly lower StO2 and NPI as well as higher TWI at the palm and fingertip in septic patients compared to healthy volunteers. StO2 and TWI showed corresponding results at the suprapatellar knee area. In septic patients, palm and fingertip THI identified survivors (E-t4) and revealed predictivity for 28-day mortality (E). Fingertip StO2 and THI correlated to SOFA-score on day 2. TWI was consistently increased in relation to the TWI range of healthy controls during the observation time. Palm TWI correlated positively with SOFA scores on day 3. - Discussion - HSI results in septic patients point to a distinctive microcirculatory pattern indicative of reduced skin oxygenation and perfusion quality combined with increased blood pooling and tissue water content. THI might possess risk-stratification properties and TWI could allow tissue edema evaluation in critically ill patients. - Conclusion - HSI technologies could open new perspectives in microcirculatory monitoring by visualizing oxygenation and perfusion quality combined with tissue water content in critically ill patients - a prerequisite for future tissue perfusion guided therapy concepts in intensive care medicine.
Gesehen am 29.07.2021